The Effect of Music Therapy on Perceived Pain, Mental Health, Vital Signs, and Medication Usage of Burn Patients Hospitalized in the Intensive Care Unit: A Randomized Controlled Feasibility Study Protocol - Ettenberger, Mark; Maya, Rafael; Salgado-Vasco, Andrés; Monsalve-Duarte, Sofia; Betancourt-Zapata, William; Suarez-Cañon, Nicolas; Prieto-Garces, Sergio; Marín-Sánchez, Juliana; Gómez-Ortega, Viviana; Valderrama, Mario (Frontiers in Psychiatry, 2021)
Background: Burn patients experience major physiological and psychological stressors during treatment and rehabilitation, including elevated levels of pain, anxiety, stress, or depression. Music interventions inclusive of music therapy (MT) have been shown to improve such symptoms, but rigorous clinical trials investigating specific music therapy methods in adult burn patients are scarce. Methods: This is a single center Randomized Controlled Trial (RCT) protocol with two parallel arms. Participants are 81 adult burn patients admitted to the Intensive Care Unit (ICU) of the University Hospital Fundación Santa Fe de Bogotá in Colombia. The intervention consists of a Music Assisted Relaxation (MAR) protocol, a music therapy technique composed of entrained live music combined with a guided relaxation and/or the use of imagery. The effects of the MAR will be compared to a control group (treatment as usual) over a period of maximum 2 weeks or six interventions. The primary outcome measure is perceived background pain, as measured with a Visual Analog Scale (VAS) before and after each intervention. Secondary outcomes are anxiety and depression levels; vital signs; and the use of pain medication. Additionally, some patients in the intervention group will be invited to participate in electroencephalography, electromyography, and electrocardiography recordings during the MAR. Discussion: This study protocol follows the SPIRIT guidelines for defining items of clinical trials and is the first study in Colombia to evaluate the effects of music therapy for adult burn patients. With this RCT it is hoped to gather new knowledge about the potential of music therapy to help critical care patients cope and recover from their injuries during the hospitalization in the ICU. Trial registration:www.clinicaltrials.gov, Identifier: NCT04571255. Protocol version: V1.0, May 24th 2021